Identification of SLC38A7 as a Prognostic Marker and Potential Therapeutic Target of Lung Squamous Cell Carcinoma. Issue 3 (September 2021) - Haratake, Naoki; Hu, Qingjiang; Okamoto, Tatsuro; Jogo, Tomoko; Toyokawa, Gouji; Kinoshita, Fumihiko; Takenaka, Tomoyoshi; Tagawa, Tetsuzo; Iseda, Norifumi; Itoh, Shinji; Yamada, Yuichi; Oda, Yoshinao; et al.
Abstract : Background: No effective molecular targeted therapy has been established for SCC. We conducted a comprehensive study of SCC patients using RNA-sequencing and TCGA dataset to clarify the driver oncogene of SCC. Method: Forty-six samples of 23 patients were totally analyzed with RNA-sequencing. We then searched for candidate-oncogenes of SCC using the TCGA database. To identify candidate oncogenes, we used the following 2 criteria: (1) the genes of interest were overexpressed in tumor tissues of SCC patients in comparison to normal tissues; and (2) using an integrated mRNA expression and DNA copy number profiling analysis using the TCGA dataset, the DNA copy number of the genes was positively correlated with the mRNA expression. Result: We identified 188 candidate-oncogenes. Among those, the high expression of SLC38A7 was a strong prognostic marker that was significantly associated with a poor prognosis in terms of both overall survival (OS) and recurrence-free survival in the TCGA dataset ( P < 0.05). Additionally, 202 resected SCC specimens were also subjected to an immunohistochemical analysis. Patients with the high expression of SLC38A7 (alternative name is sodium-coupled amino acid transporters 7) protein showed significantly shorter OS in comparison to those with the low expression of SLC38A7 protein [median OS 3.9 years (95% confidence interval, 2.4–6.4 years) vs 2.2 years (95% confidence interval, 1.9–4.1 years); log rank test: P = 0.0021]. Conclusion: SLC38A7, which is the primary lysosomal glutamine transporter required for the extracellular protein-dependent growth of cancer cells, was identified as a candidate therapeutic target of SCC. Abstract : Supplemental Digital Content is available in the text